2020
DOI: 10.1021/acscatal.0c03606
|View full text |Cite
|
Sign up to set email alerts
|

Nature’s Machinery, Repurposed: Expanding the Repertoire of Iron-Dependent Oxygenases

Abstract: Iron is an especially important redox-active cofactor in biology because of its ability to mediate reactions with atmospheric O 2 . Iron-dependent oxygenases exploit this earthabundant transition metal for the insertion of oxygen atoms into organic compounds. Throughout the astounding diversity of transformations catalyzed by these enzymes, the protein framework directs reactive intermediates toward the precise formation of products, which, in many cases, necessitates the cleavage of strong C-H bonds. In recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 208 publications
(378 reference statements)
0
87
0
1
Order By: Relevance
“…While the control of diastereo‐ and enantioselectivity is well understood for these substrates, examples of asymmetric conversions with pure carbon aromatics are scarce in classical chemistry. Enzyme catalysts provide a potential alternative to traditional Friedel‐Crafts alkylation catalysts because of their distinct advantages ranging from their operation under mild reactions conditions to their exceptional selectivity and their engineering using directed evolution [3–9] . Previous enzymes reported to catalyze Friedel‐Crafts alkylations with electrophilic coenzymes or alkyl donors include SAM‐dependent methyltransferases, [10,11] various prenyltransferases, [12–16] the recent cylindrocyclophane biosynthetic enzyme CylK, [17] artificial metalloenzymes [18] and variants of the tryptophan synthase [19–21] .…”
Section: Methodsmentioning
confidence: 99%
“…While the control of diastereo‐ and enantioselectivity is well understood for these substrates, examples of asymmetric conversions with pure carbon aromatics are scarce in classical chemistry. Enzyme catalysts provide a potential alternative to traditional Friedel‐Crafts alkylation catalysts because of their distinct advantages ranging from their operation under mild reactions conditions to their exceptional selectivity and their engineering using directed evolution [3–9] . Previous enzymes reported to catalyze Friedel‐Crafts alkylations with electrophilic coenzymes or alkyl donors include SAM‐dependent methyltransferases, [10,11] various prenyltransferases, [12–16] the recent cylindrocyclophane biosynthetic enzyme CylK, [17] artificial metalloenzymes [18] and variants of the tryptophan synthase [19–21] .…”
Section: Methodsmentioning
confidence: 99%
“…Excellent and comprehensives articles can be recommended for the interested reader. [10][11][12][13][14] The enzymes selected for this review were chosen due to a certain level of generality and broad applicability in synthesis, usually indicated by a large substrate scope. In selected cases, (industrial) examples that largely contributed to the acceptance of biocatalysis in asymmetric synthesis 15 are presented in details.…”
Section: Nonnatural Asymmetric Reactions Catalyzed By P450 Monooxygenases and Pioneered By Francesmentioning
confidence: 99%
“…It was noticed that, although the different iron forms resulted in increased % COD removal, compared to the COD removal without the supplementation of iron forms, the removal was not as high as that of the COD removal reported in other studies (e.g., Santos et al, 2008), whereby pure hydrocarbon forms were used, such as anthracene. It is suggested that the higher COD removal observed in the microbial cultures supplemented with iron was due to the higher availability of iron for induction, expression and activity of the enzymes catalyzing hydrocarbon biodegradation, as iron is a key element of oxygenases [48]. Furthermore, at low iron concentration, the direct dependence of the BS on the presence of iron, which resulted in BS over-production, probably increased hydrocarbon bioavailability to degradation, thus, leading to an increase in the % COD removal.…”
Section: Cod Removal and The Effect Of Different Iron Formsmentioning
confidence: 99%